Solvent free synthesis and structural evaluation of polyurethane films based on poly(ethylene glycol) and poly(caprolactone) - V. Kupka; L. Vojtova; Z. Fohlerova; J. Jancar (eXPRESS Polymer Letters, 2016)
Biodegradable amphiphilic polyurethane films (bio-PUs) were synthesized by solvent free polyaddition reaction of hydrophilic poly(ethylene glycol) (PEG) and hydrophobic poly(caprolactone) (PCL) as macrodiols with hexamethylene diisocyanate. Samples were subsequently heat cured in order to obtain 3D crosslinked structure. Different PCL/PEG ratios allowed controlling the toughness of the resulting bio-PUs. Significant enhancement of Young’s modulus, strength and elongation at break was observed at a PCL/PEG molar ratio above 3. The change in the bio-PU mechanical behavior was ascribed to the formation of crystalline PCL domains in the bio-PU network. The presence of PEG increased both the ability to absorb water and the rate of hydrolytic degradation, while PCL increased the cell viability. Prepared solvent free bio-PUs may advantageously be used in medicine as elastic resorbable material applicable against post-surgical adhesions.